THE ROLE OF SOCIETY AND PHILOSOPHY IN THE FORMATION OF SOCIAL AND PERSONAL COMPETENCIES - Jamalova Nargiza Ulugbek qizi (American Journals Publishing, 2023)
The purpose of the work is to show a variant of how humanitarian knowledge, in particular philosophy, can be realized and bring tangible benefits, first of all to the student. Therefore, stating the practical orientation of humanitarian knowledge, we mean its orientation to the needs of the student from the point of view of its implementation in society.
Keywords: education, philosophy, society, social and personal (universal) competences, quality of education, «self-concern».